Пам’яткознавці за покликом серця. До 20-річчя від дня заснування Харківського науково-методичного центру охорони культурної спадщини - Бахтіна, С.А. (Сіверщина в історії України, 2023)
Стаття присвячена 20-річчю Харківського науково-методичного центру охорони культурної спадщини, його внеску в справу дослідження, обстеження, виявлення, обліку, популяризації пам’яток археології, історії, монументального мистецтва м. Харкова і Харківської області. За цей час згуртований колектив фахівців і краєзнавців-аматорів провів серйозну роботу, про що свідчать пам’ятки, занесені до Державного реєстру, наукові конференції, численні наукові збірки, енциклопедії. Співробітникам Центру неодноразово приходилось мати справу з випадками порушення Закону України «Про охорону культурної спадщини», звертатись з листами до правоохоронних органів. На 2022 р. був запланований і затверджений план роботи. Після 24 лютого 2022 р. в місті ввели воєнний стан. Нічого із запланованого здійснити не вдалося. Незважаючи на тяжке становище, колектив згуртувався і продовжив роботу. А після Перемоги нас чекає обстеження пам’яток на усій території Харківської області. The article is devoted to the 20th anniversary of the Kharkiv Scientific and Methodological Center for the Protection of Cultural Heritage, its contribution to the protection, research, survey, identification, registration, and popularization of monuments of archeology, history and monumental art in Kharkiv and Kharkiv region. During this time, a united team of specialists and local historians-amateurs carried out serious work, which is evidenced by the monuments entered in the State Register, appeals to the prosecutor’s office, the police for violations of the Law of Ukraine on the Protection of Cultural Heritage”, conferences, numerous scientific collections, encyclopedias. In 2022, it was planned to conduct a survey of the monuments of the Bogodukhivskyi district, draw up accounting documentation, work in archives, libraries, write articles for the Register of monuments based on the results of the inventory, and hold regular conferences. After February 24, martial law was introduced in the city. And it was not possible to implement anything that was planned. Today the city is under rocket fire. Despite the difficult situation, the team rallied and continued to work. In November 2022 and January 2023, the Center conducted an inventory of security boards. During December 2022 - January 2023, the employees of the Center carried out a visual survey of the monuments of national importance in the city of Kharkiv, and from February 2023, they began the survey of the monuments of local importance in the city. Today it is known that two historical monuments - houses - were seriously damaged. The center continues its educational work. Employees are preparing materials for the publication of the fifth book of the encyclopedic publication “Collection of historical and cultural monuments. Kharkiv region. Chuhuiv district. Vovchansk and Starosaltivsk territorial communities”. On April 18, 2023, the Center organizes and conducts the XXVII Slobozhan readings in memory of our friend and colleague Valery Romanovsky, a historian, local historian, defender of the Motherland, who died in January of this year from a serious wound at the front. Prepared program, collection of theses. The work will continue. And after the Victory, we are waiting for work on the survey of monuments in the entire territory of the Kharkiv region.